Endogenous Oxytocin Release Eliminates In-Group Bias in Monetary Transfers With Perspective-Taking - Terris, Elizabeth T.; Beavin, Laura E.; Barraza, Jorge A.; Schloss, Jeff; Zak, Paul J. (Frontiers in Behavioral Neuroscience, 2018)
Oxytocin (OT) has been shown to facilitate trust, empathy, and other prosocial behaviors. At the same time, there is evidence that exogenous OT infusion may not result in prosocial behaviors in all contexts, increasing in-group biases in a number of studies. The current investigation seeks to resolve this inconsistency by examining if endogenous OT release is associated with in-group bias. We studied a large group of participants (N=399) in existing groups and randomly formed groups. Participants provided two blood samples to measure the change in oxytocin after a group salience task and then made computer-mediated monetary transfer decisions to in-group and out-group members. Our results show that participants with an increase in endogenous OT showed no bias in monetary offers in the ultimatum game to out-group members compared to in-groups. There was also no bias in accepting ultimatum game offers, though in-group bias persisted for a unilateral monetary transfer. Our analysis shows that the strength of identification with one's group diminished the effects that an increase in OT had on reducing bias, but bias only recurred when group identificaion reached 87% of its maximum value. Our results indicate that the endogenous OT system appears to reduce in-group bias in some contexts, particularly those that require perspective-taking.